Climate change and mapping hazard risk and vulnerability in mountain ecosystem: A case study of Himachal Himalaya - Sneh Gangwar (National Geographical Journal of India, 2023)
The Himalayas represents a vast mountain system and is globally valued for their significant role in the regulation of global as well as the regional climate that has a direct impact on biodiversity and ecosystem services crucial for the sustenance of millions of people in the Himalayas and adjoining areas. Climate change in the Himalayan region has implications for food production, natural ecosystems, the retreat of glaciers, water supply, human and animal health and overall human well-being. There is a severe gap in the dissemination of knowledge of the short and long-term implications of climate change in the Himalayas and in downstream. An introspection of the status of the vulnerability of the Western Himalayan ecosystem to climate change due to ecological fragility, scarcity of resources and increase in disaster occurrence shows a need to strengthen local knowledge, innovations, and practices within social and ecological systems as well as strengthening the functioning of institutions relevant for adaptation. The study is useful to policy makers to design appropriate adaptation strategies to cope with the impacts of climate changes in the area.